Method and new distributor for delivering high velocity gas from a gas distributor through a nozzle with decreased erosion in the nozzle - MACLEAN; JOHN P; LIONETTI; THOMAS A (1984)
A method as described in the title comprising deflecting the gas from the distributor through nozzles therein through an angle in the range of 30 DEG to 75 DEG for decreased erosion in the nozzles by solids drawn therein and for reduced required power consumption. A new gas distributor with nozzles mounted therein is disclosed.